IOT IMPLEMENTATION IN SMART BUILDING USING THE FUZZY METHOD - Joseph Dedy Irawan; Thomas Priyasmanu; Renaldi P. P; Sentot Achmadi (Computer Science Department, Malang National Institute of Technology, 2024)
With the advancement of internet technology, it is very easy for humans in the field of information, one implementation that utilizes this technology is the internet of things, where this technology connects electronic devices with internet technology, so that the equipment can be monitored and controlled remotely, one of the advantages of technology In this case, all electronic devices can be modified to make it easier for us to monitor and control according to our needs. By combining the fuzzy logic method, electronic devices that are connected to the internet will become smarter, because the electronic equipment can automatically adjust its condition according to the needs of its owner. In this research, the combination of internet of things and fuzzy logic technology will be implemented in smart buildings, with the hope that the condition of the building will run automatically, depending on the natural conditions that occur